Alley cropping on an ultisol in southeastern Nigeria - Meregini, A.O.; Okoro, E.G.; Kang, B. (1995)
An alley cropping trial was carried out on an acidic Typic paleudull in the humid forest zone of southeastern Nigeria using Three indigenous (Anthonotha macrophylla, Dactyladenia barteri, Harungana madagascariensis and two exotic (Calliandra calothyrsus and Flemingia macrophylla) hedgerow species. Early growth of Anthonotha was slow. Harungana and calliandra could not withstand repeated pruning and died 3 to 4 years after establishment. Dactyladenia performed better than Anthonata and Flemingia. Alley cropping did not have any distinct effect on soil properties. Among alley cropped plots, cassava yield was highest in Flemingia and Dactyladenia plots, while the control plot recorded the lowest yield. Cowpea yields were high in Calliandra and Dactyladenia plots Dactyladenia plots were the least infested with weeds. Dacryladenia and Flemingia appeared to be suitable species for alley cropping on acid soils allow altitude.